2002
DOI: 10.1590/s1676-24442002000300005
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antimicrobiana in vitro de quinupristina/dalfopristina para cocos gram-positivos isolados de cinco centros brasileiros: resultado do estudo de vigilância L-SMART

Abstract: Há alguns anos tem-se verificado um aumento progressivo da resistência de alguns cocos gram-positivos a determinados antimicrobianos. Este aumento da resistência tem sido observado principalmente no ambiente hospitalar, e as bactérias mais comumente envolvidas são os Staphylococcus spp. e os Enterococcus spp. Devido a este fato, novos antimicrobianos são avaliados para o tratamento de infecções causadas por estas cepas multirresistentes. A associação quinupristina/dalfopristina (Q/D), também conhecida como Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…34 In this work, despite presenting excellent efficacy in the majority of the studied CoNS, intermediate resistance to this drug was detected in two S. epidermidis and one S. hemolyticus. In the study conducted by Mendes et al, 35 quinupristin/dalfopristin demonstrated excellent effectiveness for CoNS, the strains were fully susceptible, with MIC 90 values of 0.38 μg/mL for the oxacillin-susceptible strains and 0.75 μg/mL for the oxacillin resistant strains. In addition, Venkatesh et al 36 described good effectiveness of quinupristin/dalfopristin for oxacillin resistant and susceptible strains.…”
Section: Discussionmentioning
confidence: 93%
“…34 In this work, despite presenting excellent efficacy in the majority of the studied CoNS, intermediate resistance to this drug was detected in two S. epidermidis and one S. hemolyticus. In the study conducted by Mendes et al, 35 quinupristin/dalfopristin demonstrated excellent effectiveness for CoNS, the strains were fully susceptible, with MIC 90 values of 0.38 μg/mL for the oxacillin-susceptible strains and 0.75 μg/mL for the oxacillin resistant strains. In addition, Venkatesh et al 36 described good effectiveness of quinupristin/dalfopristin for oxacillin resistant and susceptible strains.…”
Section: Discussionmentioning
confidence: 93%
“…Antimicrobial resistance among pathogens commonly causing community‐acquired respiratory tract infections (RTIs) is a global problem, although the prevalence of resistance varies considerably by region as a result of numerous variables, such as differences in prescribing practice, dosage of drug used, or (among Streptococcus pneumoniae isolates) predominant serotype. National and international surveillance programmes have played an important role in documenting resistance patterns of the common respiratory tract pathogens, S. pneumoniae , Haemophilus influenzae and Moraxella catarrhalis [1–3].…”
Section: Introductionmentioning
confidence: 99%
“…National and international surveillance programmes have played an important role in documenting resistance patterns of the common respiratory tract pathogens, S. pneumoniae, Haemophilus influenzae and Moraxella catarrhalis [1][2][3].…”
mentioning
confidence: 99%